Comparison of the laparoscopic transperitoneal pyeloplasty to the extraperitoneal open and retroperitoneoscopic approaches in children: technical aspects and early outcomes from a developing practice - Mahmoud Marei Marei; Supul Hennayake; Tamás Cserni (Egyptian Pediatric Association Gazette)
Abstract Introduction Retroperitoneal pyeloplasty (RP) was thought to be associated with fewer possible complications than the transperitoneal approach (TP); however, TP offers larger working space and an easier anastomosis, anterior to crossing lower pole vessels, when present. In TP, the peritoneum can be easily reconstructed back, and cosmesis is nearly similar. We reviewed our experience with RP and TP in comparison with the classic open extra/retroperitoneal approach (OP). Material and methods Data from 156 cases who had pyeloplasty were reviewed: TP: 40 consecutive cases (27 over 5 years old, 13 under 5 years old and 3 under 1 year old; youngest - 5 months old), including 3 redo/revision cases; RP: 56 consecutive primary cases, all over 5 years of age; and OP: 60 primary cases (41 over 5 years old, 19 under 5 years old, and 9 under 1 year old; youngest - 3 months old). Operation time, conversion rate, and complications were all compared. Unpaired t-test and chi-square test were used, and p < 0.05 was considered significant. Results There were no intraperitoneal surgical complications such as organ injury or bowel adhesions with TP. TP was operatively shorter than RP (230.4 ± 29 vs. 249.8 ± 46 min, p = 0.0036). The conversion rate was lower in TP than in RP [1/40 (2.5%) vs. 3/56 (5%), p = 0.380]. There was neither a difference in hospital stays (both 3 days) nor a statistically significant difference in postoperative complications requiring intervention as JJ stenting, balloon dilatation, and redo/revision pyeloplasty [TP: 4/40 (10%) vs. RP: 4/56 (7%), p = 0.6003, and vs. OP: 5/60 (8%), p = 0.7308)]. Conclusion TP is safe, effective, and relatively shorter than RP and suitable for much younger patients and redo/revision pyeloplasties. Transperitoneal pyeloplasty remains a viable and justifiable option for developing and aspiring paediatric surgeons and urologists.